Perencanaan Arsitektur Enterprise Menggunakan TOGAF ADM (Studi Kasus: Kantor Desa Lembang) - Desy Angeline; Charitas Fibriani (Journal of Information System and Informatics, 2021)
The Lembang Village Office is a government institution that operates at the Village level in the Bengkayang Regency area. The Lembang Village Government has not implemented an Information System in carrying out its duties, this can be seen from the obstacles faced by the Village government. The obstacles faced are the frequent accumulation of old data, so it is difficult when it will be recorded again, even usually there is data lost so it requires a system that can help data storage. The purpose of this research is to provide directions or directions to be able to implement an information system for data storage. performance in the future, the method used this time is TOGAF (The Open Group Architecture Framework) ADM (Architecture Development Method).This research will produce a blueprint and provide a roadmap using the elements that exist in the togaf at the Lembang Village Office in order to implement an information system on future performance.